Lost in legal translation: language rights, interpreter mediation, and procedural inequality in Indonesia’s multilingual courtrooms - Gerry Kadamehang (Indonesian Journal of Linguistics and Legal Discourse, 2026)
Background: Indonesia’s multilingual legal order places courtroom language access at the centre of fair-trial protection, because defendants, witnesses, and justice seekers may encounter state law through Bahasa Indonesia, foreign languages, regional languages, indigenous languages, or sign-language mediation in criminal and civil proceedings. Objective: This study examines how language rights, interpreter mediation, and procedural inequality are articulated across public Indonesian legal and courtroom-related materials. Method: Using a qualitative corpus-assisted sociolegal design, this study analyses 34 public documents comprising legal norms, court-service texts, courtroom event reports, contextual human-rights standards, and scholarly sources, coded through a language-rights matrix, an interpreter-mediation grid, and a procedural-inequality register. Results: The findings show that language access is recognised across several institutional registers, but its operational mechanism is unevenly specified. Interpreter mediation becomes most visible when multilingualism disrupts ordinary courtroom procedure, especially in foreign-defendant cases, disability-related access, remote testimony, or documented interpreter presence. Implication: Procedural inequality appears as a gap between formal audibility and effective participation, where understanding, response, repair, and accountability remain unevenly distributed. Novelty: The novelty of this study lies in reframing courtroom interpreting in Indonesia as a condition of mediated legal participation rather than a technical supplement to legal translation within multilingual justice systems and access-to-justice research.